BURDEN AND SPECTRUM OF RESPIRATORY AILMENTS IN PAEDIATRIC TERTIARY CARE SETTING - Bibi, Saima; Syed Yasir Hussain Gilani; Tahir Saeed Siddiqui; Afsheen Siddiqui; Shahzad Najeeb; Hafiza Sidra (Journal of Ayub Medical College Abbottabad, 2021)
Background: Respiratory tract infections are a significant cause of mortality and morbidity in paediatric age group all over the world and especially in under developed regions. The present study was conducted with an aim to assess the burden and the types of respiratory illnesses in our region. Methods: The study was a cross sectional study conducted at Paediatric A unit of Ayub teaching hospital from 1st October, 2018 to 31st March, 2019. All patients aged 1 month and above who required admission for various respiratory ailments were included in the study. Results: A total of 2255 patients were admitted in Paediatric A unit over a six months period. Of these, 603 (26.74%) patients were admitted with various respiratory problems and were included in the study. Among these, 389 (64.5%) patients were male and 214 (35.5%) were female. Mean age of the participants was 18.77±30.87 months. The major disease categories were bronchopneumonia in 189 (31.3%), bronchiolitis in 176 (29.2%), measles pneumonia in 60 (10%), lobar pneumonia in 52 (8.6%) and upper RTI in 32 (5.3%). Mean duration of stay was 3.13±2.08 days. Majority of the patients 482 (79.9%) were up to 24 months of age, followed by 77 (12.8%) patients in 25-60 months age and 44 (7.3%) patients more than 60 months of age. A total 295 (48.92%) patients were vaccinated while 308 (51.07%) patients were either partially vaccinated 116 (19.2%) or unvaccinated 192 (31.8%). A total of 576 (95.5%) patients were discharged, 17 (2.8%) patients expired and 5 (0.8%) were referred to higher specialty. Bronchopneumonia was the leading cause of mortality in this study. Conclusion: Respiratory tract infections constitute a major threat to the health of paediatric patients especially in the first two years of life. Improvement in vaccination coverage is essential in reducing the burden of a majority of respiratory ailments along with health education. Keywords: Respiratory tract infections; Pneumonia; Mortality